Oral Midazolam Vs Promethazine as Pre Sedation Medication in Pediatric Dentistry - Ansari, Ghassem; Razavi, Shiva; Toomarian, Lida; Eghbali, Ahmad; Shayeghi, Shahnaz (Journal of Dental School, 2018)
Objectives Pre- and post-sedation effect of oral Midazolam to promethazine in2-6 yrs old fearful children for dental treatment Methods This randomized clinical trial was carried out on a group of 26 children aged 2-6 years referred to the dental school due to their fear and multiple dental needs. Patients were selected from ASA I or II classification and scored 1 in Frankl Behavior scale. Each patient was scheduled for two subsequent visits to receive one of the two pre medications before IV sedation. Each patient served as self-control and randomly assigned to either group A: receiving Midazolam oral as premed in 1st visit or group B: receiving Promethazine oral as the premed in 1st visit. Six hour NPO was instructed prior to sedation visit. Monitoring vital signs were conducted at every 15 minutes starting with base line before any drug administration. Sedation score was recorded using Houpt Sedation scale. Post sedation problems were recorded by operator. Data were analyzed using Student t test and Kruskal Wallis. Results No significant difference was noted between the patient perceptions at the two different visits. Children did not show a significant difference on symptoms such as Crying, Movement, Sleep and overall behavior in two visits at the first 15 minutes of sedative injection. Post-operative complications were having no significant difference. Lower sickness and vomiting were reported following promethazine intake. Conclusion Promethazine seems to be as effective and as acceptable premedication as Midazolam in pediatric dentistry.